Influence of microstructure and manganese sulfides on corrosion resistance of selective laser melted 17-4 PH stainless steel in acidic chloride medium. (15th May 2020) - Alnajjar, Michella; Christien, Frédéric; Barnier, Vincent; Bosch, Cédric; Wolski, Krzysztof; Fortes, A. Dominic; Telling, Mark
Highlights: The as-built SLM-ed 17-4 PH steel was ferritic in contrast to the martensitic wrought steel. After re-austenization treatment the SLM-ed steel recovered the martensitic microstructure. The as-built and re-austenitized steels had similar general corrosion resistance. The re-austenitized steel had superior general corrosion resistance than the wrought steel. MnS inclusions destabilized the passive film of the wrought steel, but they did not have any effect on pitting corrosion. Abstract: The corrosion resistance of 17-4PH stainless steel obtained by Selective Laser Melting was investigated. It was found that the as-built SLM-ed steel was entirely ferritic, not martensitic as expected. Re-austenitized SLM-ed steel recovered the martensitic microstructure. The two SLM-ed steels (as-built and re-austenitized) had the same general corrosion resistance which was correlated with their similar chemical composition. The martensitic re-austenitized SLM-ed steel had superior general corrosion behavior than the wrought martensitic steel. This was due to the nearly absence of MnS inclusions in the re-austenitized SLM-ed steel, while their presence in the wrought steel destabilized the passive film.